Pembinaan Spiritualitas Remaja Sekolah melalui Program “Renungan Pagi Bersama” di SMA Elpida Noelbaki - Elisabet Dethan; Ferdinand Benu; Hilda Tunliu; Erni Paji jerah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2022)
This community service program aims to strengthen the spiritual formation of Christian adolescents through the “Morning Devotion Together” program at Elpida Senior High School Noelbaki. Adolescence is a crucial phase in shaping identity and faith maturity, where students often face moral and spiritual challenges due to digital culture and social pressure. Therefore, a contextual and continuous spiritual formation program is essential in the school environment. The Morning Devotion Together program was designed as a weekly routine consisting of Bible reading, short reflection, and prayer, led alternately by teachers and students. The implementation method included assessing students’ spiritual needs, preparing devotional materials, training student facilitators, and providing mentoring during the program. The results showed increased student participation in spiritual activities (85%), improvement in personal prayer habits (72%), and stronger teacher–student spiritual relationships. The program also fostered a Christ-centered school culture and served as a model for faith development in Christian education. Thus, the Morning Devotion Together program proved effective in nurturing character, strengthening spirituality, and integrating Christian values into the daily life of the school community.